Detection of SARS-CoV-2 N-antigen in blood during acute COVID-19 provides a sensitive new marker and new testing alternatives. (May 2021) - Le Hingrat, Quentin; Visseaux, Benoit; Laouenan, Cedric; Tubiana, Sarah; Bouadma, Lila; Yazdanpanah, Yazdan; Duval, Xavier; Burdet, Charles; Ichou, Houria; Damond, Florence; Bertine, Melanie; Benmalek, Nabil; et al.
Abstract: Objectives: Molecular assays on nasopharyngeal swabs remain the cornerstone of COVID-19 diagnostics. The high technicalities of nasopharyngeal sampling and molecular assays, as well as scarce resources of reagents, limit our testing capabilities. Several strategies failed, to date, to fully alleviate this testing process (e.g. saliva sampling or antigen testing on nasopharyngeal samples). We assessed the clinical performances of SARS-CoV-2 nucleocapsid antigen (N-antigen) ELISA detection in serum or plasma using the COVID-19 Quantigene® (AAZ, France) assay. Methods: Performances were determined on 63 serum samples from 63 non-COVID patients and 227 serum samples (165 patients) from the French COVID and CoV-CONTACT cohorts with RT-PCR-confirmed SARS-CoV-2 infection, including 142 serum samples (114 patients) obtained within 14 days after symptom onset. Results: Specificity was 98.4% (95% CI 95.3–100). Sensitivity was 79.3% overall (180/227, 95% CI, 74.0–84.6) and 93.0% (132/142, 95% CI, 88.7–97.2) within 14 days after symptom onset. Ninety-one of the included patients had serum samples and nasopharyngeal swabs collected in the same 24 hr. Among those with high nasopharyngeal viral loads, i.e. Ct value below 30 and 33, only 1/50 and 4/67 tested negative for N-antigenaemia, respectively. Among those with a negative nasopharyngeal RT-PCR, 8/12 presented positive N-antigenaemia; the lower respiratory tract was explored for six of these eight patients, showing positive RT-PCR in five cases. Discussion: This is the first evaluation of a commercially available serum N-antigen detection assay. It presents a robust specificity and sensitivity within the first 14 days after symptoms onset. This approach provides a valuable new option for COVID-19 diagnosis, only requiring a blood draw and easily scalable in all clinical laboratories.